Implantation of an Artificial Endothelial Layer for Treatment of Chronic Corneal Edema. Issue 12 (21st December 2021) - Auffarth, Gerd U.; Son, Hyeck-Soo; Koch, Matthias; Weindler, Jan; Merz, Patrick; Daphna, Ofer; Marcovich, Arie L.; Augustin, Victor A.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Purpose: The purpose of this study was to describe a novel device that may serve as an alternative to Descemet membrane endothelial keratoplasty (DMEK) for the treatment of chronic corneal edema. Methods: The EndoArt (EyeYon Medical, Israel) is a flexible, 50-μm thin artificial endothelial layer that matches the cornea's posterior curvature and functions as a fluid barrier at the posterior stroma, replacing the diseased endothelium. Similar to a DMEK approach, it is implanted into the anterior chamber, carefully positioned on the posterior stroma, and secured using an air–gas mixture. Two patients with chronic corneal edema resulting from endothelial decompensation underwent implantation of the new artificial lamella. Results: In patient 1, the central corneal thickness (CCT) decreased from 730 μm preoperatively to 593 μm at 1 day postoperatively. In patient 2, the CCT decreased from 761 μm preoperatively to 487 μm at 1 day postoperatively. Both patients reported high satisfaction and an overall brighter visual quality. Although dislocation of the lamella occurred in both cases, the CCT was promptly restored after a repositioning procedure and remained stable at the 17-month follow-up (CCT of 526 and 457 μm for patients 1 and 2, respectively). In contrast to DMEK donor tissue, the artificial lamella is sufficiently robust to allow easy intraocular manipulation without the risk of damaging the implant. It is easily removable and does not require any immunosuppressive treatment because of its nonbiological nature. Conclusions: Implantation of the EndoArt led to rapid corneal deturgescence and CCT restoration, presenting a possible option for patients with chronic corneal edema.